Effect of parameters: on the electroplating of Ni-Co alloys in an ammonium citrate bath on Yellow Brass (C27200) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Ni-Co alloy coatings are electroplated from a solution of nickel sulfate with Co suspension on a copper substrate. Then study the factors affecting the precipitation of Ni-Co alloys from a citric acid and ammonium citrate bath (The impact of the bath's carbon dioxide content and current density on the sediment's carbon dioxide content). The optimal conditions were C.D.2A/dm2, temperature 55°C, time 60 minutes, pH 8. Characterization of the coating layer in terms of (surface shape, composition of the coated layer, hardness measurements).by studying sedimentary surfaces by SEM, thin films by X-ray diffraction, and Vickers microhardness. It was found that the largest surface hardness value was at the current density of 2 A/dm2 (470HV).